Radio Frequency Identification (RFID) Indoor Parking Control System - El-Hageen, Hazem M. M.; Mohammad Ata, Karimeh Ibrahim; Che Soh, Azura; Ishak, Asnor Juraiza; Jaafar, Haslina (Research Publication, 2017)
Frequency Identification (RFID) Parking Control System is a control and monitoring system designed for using at residential condominiums, gated communities, business parking garages, university parking areas, and hospitality or retail centers. In this study, a parking management system is designed using RFID technology along with wireless RF ZigBee to control and manage parking for mall workers. This system identifies each vehicle with a RFID-TAG/CARD using the mall worker card at the gate. The data will be exchange between the computer located at the gate and the sensors located at the garage through wireless RF ZigBee to clarify the empty parking place. Based on the data, the dynamic programming algorithm embedded in the system will determine the nearest parking location based on their entrance destination to the worker. The system can automatically monitor, guide and localize the nearest parking to the workers inside the parking space.